A comparison of different bedside techniques to determine endotracheal tube position in a neonatal piglet model1. Issue 2 (21st May 2012) - Schmölzer, Georg M.; Bhatia, Risha; Davis, Peter G.; Tingay, David G.
Abstract Rationale Endotracheal tube (ETT) malposition is common and an increasing number of non‐invasive techniques to aid rapid identification of tube position are available. Electrical impedance tomography (EIT) is advocated as a tool to monitor ventilation. Objective This study aimed to compare EIT with five other non‐invasive techniques for identifying ETT position in a piglet model. Methodology Six saline lavage surfactant‐depleted piglets were studied. Periods of ventilation with ETT placed in the oesophagus or a main bronchus (MB) were compared with an appropriately placed mid‐tracheal ETT. Colorimetric end‐tidal CO2 (Pedi‐Cap®), SpO2 and heart rate, tidal volume ( <![CDATA[V_T_ao ]]> <inline-graphic xlink:href="ark:/27927/pgg1q9kw3gg" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />) using a hot‐wire anemometer at the airway opening, tidal volume using respiratory inductive plethysmography ( <![CDATA[V_T_RIP ]]> <inline-graphic xlink:href="ark:/27927/pgg1q9kw3z6" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />) and regional tidal ventilation within each hemithorax (EIT) were measured. Results Oesophageal ventilation: Pedi‐Cap® demonstrated absence of color change. <![CDATA[V_T_ao ]]> <inline-graphic xlink:href="ark:/27927/pgg1q9kw3xn" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />, <![CDATA[V_T_RIP ]]> <inline-graphic xlink:href="ark:/27927/pgg1q9kw3w3" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />, and EIT correctly demonstrated no tidal ventilation. SpO2 decreased from mean (SD) 96 (2)% to 74 (12)% (P < 0.05; Bonferroni post‐test), without heart rate change. MB ventilation: SpO2, heart rate and Pedi‐Cap® were unchanged compared with mid‐tracheal position. <![CDATA[V_T_ao ]]> <inline-graphic xlink:href="ark:/27927/pgg1q9kw3vj" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> and <![CDATA[V_T_RIP ]]> <inline-graphic xlink:href="ark:/27927/pgg1q9kw3t0" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> decreased from a mean (SD) 10.8 (5.6) ml/kg and 14.6 (6.2) ml/kg to 5.5 (1.9) ml/kg and 6.4 (2.6) ml/kg (both P < 0.05; Bonferroni post‐test). EIT identified the side of MB ventilation, with a mean (SD) 95 (3)% reduction in tidal volume in the unventilated lung. Conclusions EIT not only correctly identified oesophageal ventilation but also localized the side of MB ventilation. At present, no one technique is without limitations and clinicians should utilize a combination in addition to clinical judgement. Pediatr Pulmonol. 2013; 48:138–145. © 2012 Wiley Periodicals, Inc.